STORY OF COHESION ON THE HISTORY OF AN ACADEMIC INSTITUTION - Zachar Podolinská, Tatiana (Ethnological studies, 2023)
This book is a contribution to the anthropology of academic institutions in Central Europe from the latter half of the 20th century until nowadays. On the background of longue durée processes and profound political, ideological, and economic transformations, the book displays the micro-temporalities in the life of the Institute of Ethnology and Social anthropology within the Slovak Academy of Sciences. The book offers critically self-reflective combination of the anthropological perspective, historical ethnography, and memory studies. Besides using the archive, printed and electronic sources, the Authors also conducted comprehensive qualitative research among the members of the Institute to capture imprints of the internalised (hi)stories, attitudes, feelings, and emotions. Using qualitative ethnography, the Authors also pictured the intimate atmosphere and very nature of the Institute as a living organism during the socialist, post-socialist, and post- transitional era. Tracing the internal history of the Institute based on the generations of Founders and Builders, and the Transformation and Innovation generations, the Authors discovered that what is essential in the success of the Institute is a strong positive auto-narrative of internal cohesion and team support, transmitted from one generation to another as a precious legacy.